2021
DOI: 10.1080/13880209.2021.1878238
|View full text |Cite
|
Sign up to set email alerts
|

Icariin improves brain function decline in aging rats by enhancing neuronal autophagy through the AMPK/mTOR/ULK1 pathway

Abstract: Context: Icariin (ICA) is the main active ingredient of Epimedium brevicornu Maxim (Berberidaceae), which is used in the immune, reproductive, neuroendocrine systems, and anti-aging. Objective: To evaluate the effect of ICA on natural aging rat. Materials and methods: 16-month-old Sprague-Dawley (SD) rats were randomly divided into aging, low and high-dose ICA groups (n ¼ 8); 6-month-old rats were taken as the adult control (n ¼ 8). Rats were fed regular feed (aging and adult control) or feed containing ICA (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 57 publications
0
36
0
Order By: Relevance
“…Xia et al have demonstrated that, in aged rats, Epimedium flavonoids and icariin attenuate the proinflammatory response while enhancing an anti-inflammatory response in inter alia the hippocampus, hypothalamus, and hypophysis, and mitigate neuroinflammation in aging [ 512 , 513 ]. Icariin acts via the AMPK/mTOR/ULK1 pathway to increase neuronal autophagy and enhance brain function in aged Sprague–Dawley (SD) rats [ 514 ]. Moreover, in the bilateral common carotid arteries occlusion (BCCAO) rat model of AD, which manifests as neuronal morphological damage along with Aβ deposition in the hippocampus and cognitive deficits of Aβ in rat hippocampus, oral administration of icariin reduces hippocampal expression of APP and BACE1, and induces the expressions of insulin-degrading enzyme (IDE) and a disintegrin and metalloproteinase domain 10 (ADAM10).…”
Section: Possible Intervention For Neuroinflammation In Admentioning
confidence: 99%
“…Xia et al have demonstrated that, in aged rats, Epimedium flavonoids and icariin attenuate the proinflammatory response while enhancing an anti-inflammatory response in inter alia the hippocampus, hypothalamus, and hypophysis, and mitigate neuroinflammation in aging [ 512 , 513 ]. Icariin acts via the AMPK/mTOR/ULK1 pathway to increase neuronal autophagy and enhance brain function in aged Sprague–Dawley (SD) rats [ 514 ]. Moreover, in the bilateral common carotid arteries occlusion (BCCAO) rat model of AD, which manifests as neuronal morphological damage along with Aβ deposition in the hippocampus and cognitive deficits of Aβ in rat hippocampus, oral administration of icariin reduces hippocampal expression of APP and BACE1, and induces the expressions of insulin-degrading enzyme (IDE) and a disintegrin and metalloproteinase domain 10 (ADAM10).…”
Section: Possible Intervention For Neuroinflammation In Admentioning
confidence: 99%
“…Icariin, including its active metabolic metabolites and semi-synthetic derivatives, has evolved to be an anti-aging molecule with stimulating effects on age-related diseases. Icariin enhanced brain function in aging rodents by increasing neuronal autophagy ( Zheng et al, 2021 ). This ability of icariin to induce neuronal autophagy/mitophagy was via the AMPK/mTOR/ULK1 pathway, suggesting that it can modulate intrinsic nutrient-sensing signaling to engage the cellular trash management system effectively ( Wang et al, 2021a ; Zheng et al, 2021 ).…”
Section: Clinical Utility and Control Of Biological Aging And Age-rel...mentioning
confidence: 99%
“…In addition, several studies have proved that ageing is accompanied by dysfunctional autophagy [ 118 ]. Icariin reduces neuronal dysfunction in ageing rats by promoting neuronal autophagy through the AMPK/mTOR/ULK1 pathway [ 119 ]. Icariin could ameliorate the motor and learning disabilities of male C57BL/6J ageing mice by activating Akt/Nrf2/NF-ĸB signaling pathway [ 117 ].…”
Section: Pharmacodynamics Of Icariin On Ageingmentioning
confidence: 99%